دراسة انهیارات و تشققات الأبنیة المنفذة على الترب الطینیة و طرق تدعیمها - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2007)
This study was involved with the diffferent types of cracks and reptures that may occur in structures, also a practical case for a school building in Al – Ramadi city is presented in this work. Necessary and instantenuos ways for treatments were suggested in this study.It was obvious that this building needs to support footing .In addition, supporting the columns and concrete beams was included in the present work